Designing and testing a module based on the integrated approach between the subjects of geography and natural sciences. A case study of the common core science stream in the Moroccan high school - Soulali, Abdelali (Journal of Educational and Psychological Sciences, 2023)
The work falls within the studies that aim to develop the curricula in the Moroccan school. It aims to present the results of an experimental study related to the design and testing of a module learning based on the integrative approach between the subjects of geography and natural sciences. It is based on the implementation of the component of extensions and intersections between the two subjects program at the level of the common core of science stream. The study adopted the experimental and descriptive analytical approaches, descriptive and inferential statistics, and the use of pre- and post-test tool in the experiment on the two groups: The control and the experimental. The study concluded that the experimental group outperformed the control group at the level of achievement results, whether in relation to general results or detailed results, and at the level of all learning domains. This made it possible to present a set of proposals for implementation of the component of extensions and intersections between the school subjects within the Moroccan educational curriculum.